Loss of Substitutability: A Note of Disparity between WTP and WTA - Dragicevic, Arnaud Z. (Journal of Environmental Science and Engineering Technology, 2024)
This note examines the disparity between willingness-to-pay (WTP) and willingness-to-accept (WTA) in the nonmarket valuation of environmental public goods. We observe that the commonly cited substitution effect and endowment effect, while often used to explain this disparity, address distinct conceptual questions. Building on this, we propose an integrated model that incorporates both effects within a reference-dependent framework. Our findings demonstrate that compensation demanded for lost substitutability is unbounded under a neoclassical framework but constrained within a loss-aversion context. These results offer a foundation for empirical testing to advance understanding of this persistent issue.